Please answer question number 19 and 21
Attachments:
![](https://hi-static.z-dn.net/files/d72/9577af8300c462baaa90ce1ca3804d40.jpg)
Answers
Answered by
2
_______________________________
(1) H.C.F
( xy + x^2 ),( xy - x^2 ) , ( x^4 - x^2 y^2 )
= x ( y + x , y - x , x^3 - x y^2 )
H.C.F = x
_______________________________
(2) H.C.F ( 36 x^2 y^3 , 32x^3 y^2 )
= 4x^2 y^2 ( 9y , 8 x )
H.C.F = 4 x^2 y^2
_______________________________
L.C.M ( 36 x^2 y^3 , 32 x^3 y^2 )
_______________________________
36 x^2 y^3 = 2 × 2 × 3 × 3 × x^2 × y^3
32 x^3 y^2= 2 × 2 × 2 × 2 × 2 × x^3 × y^2
_______________________________
36 x^2 y^3 = 2^2 × 3^2 × x^2 × y^3
32 x^3 y^2 = 2^5 × x^3 × y^2
_______________________________
Required
L.C.M = 2^5 × 3^2 × x^3 × y ^3
= 32 × 9 × x^3 × y^3
= 288 x^3 y^3
_______________________________
(1) H.C.F
( xy + x^2 ),( xy - x^2 ) , ( x^4 - x^2 y^2 )
= x ( y + x , y - x , x^3 - x y^2 )
H.C.F = x
_______________________________
(2) H.C.F ( 36 x^2 y^3 , 32x^3 y^2 )
= 4x^2 y^2 ( 9y , 8 x )
H.C.F = 4 x^2 y^2
_______________________________
L.C.M ( 36 x^2 y^3 , 32 x^3 y^2 )
_______________________________
36 x^2 y^3 = 2 × 2 × 3 × 3 × x^2 × y^3
32 x^3 y^2= 2 × 2 × 2 × 2 × 2 × x^3 × y^2
_______________________________
36 x^2 y^3 = 2^2 × 3^2 × x^2 × y^3
32 x^3 y^2 = 2^5 × x^3 × y^2
_______________________________
Required
L.C.M = 2^5 × 3^2 × x^3 × y ^3
= 32 × 9 × x^3 × y^3
= 288 x^3 y^3
_______________________________
maitri24:
thanks for answering
Similar questions